The effect of heat-sensitive moxibustion in the elderly with nocturia: protocol for a randomized controlled trial - Geng, Jinhua; Ma, Xintong; Lin, Yihui; Lin, Qiaoli; Wen, Kaitian; Ruan, Chunyan; Li, Zunjiang; Mo, Zhaofan; Li, Shuang; Ding, Banghan; Liu, Na (Frontiers in Medicine, 2025)
BackgroundNocturia is a common and bothersome symptom in the elderly population, significantly impacting their quality of sleep and overall well-being. Heat-Sensitive moxibustion (HSM) is effective for elderly people with nocturia, but its efficacy has not been scientifically proven. This randomized controlled trial is designed to determine the efficacy and safety of HSM in the elderly with Nocturia.MethodThis study is designed as a randomized, single-blind clinical trial, focusing on a population of 110 patients aged 60 and above who suffer from non-specific nocturia lasting for at least 1 month. Patients in the intervention arm are scheduled for 2 cycles of HSM, while patients in the control group will undergo the same cycle of conventional treatment. To ensure objectivity, assessors and investigators will remain blinded to the randomization process. The primary outcome of this study is the reduction in the frequency of nocturia. Additionally, several secondary outcomes will be evaluated, including sleep quality, quality of life scores, the efficacy of traditional Chinese medicine (TCM) syndrome, and changes in blood biomarkers Arginine vasopressin (AVP) and Atrial natriuretic peptide (ANP). These assessments will be conducted at baseline, post-intervention and at the 2-month follow-up to comprehensively evaluate the effectiveness and safety of HSM.DiscussionIn this study, we aim to quantitatively analyse the therapeutic effect and safety of HSM on nocturia in the elderly, clarify the amount of moxibustion, the distribution pattern of heat-sensitized acupoints, the frequency of heat-sensitized acupoints, and the moxibustion sensation for the treatment of senile nocturia, which can bring insights into future clinical treatments.